Խորհրդային զորքերի մուտքը Արցախ - Գևորգյան, Համլետ
28 апреля 1920 года советские войска под руководством Тухачевского вошли в Баку и объявили Мусаватский Азербайджан Советским Азербайджаном. Затем, до 20 мая, под руководством армянских большевиков Красная Армия вторглась в ряд районов Арцаха и повсеместно установила советскую власть. В такой ситуации лидер вооруженных сил Арцах-Зангезур Дро вынужден был заставить советские войска покинуть земли Арцаха или позволить Арцаху стать советским. В сложившейся ситуации он предусмотрительно выбрал второй вариант и избежал конфронтации с советскими войсками. Оставив власть армянским большевикам, он покинул Арцах со своей военной частью. On April 28 of 1920, Soviet troops under the leadership of Tukhachevsky entered Baku and declared Musavat Azerbaijan as Soviet Azerbaijan. Then, until May 20, under the guidance of the Armenian Bolsheviks, the Red Army invaded a number of regions of Artsakh and established the Soviet rule everywhere. In such situation the leader of Artsakh-Zangezur armed forces Dro had to force the Soviet armies to leave the lands of Artsakh or to let Artsakh become Soviet. In current situation, he prudently chose the second option and avoided confrontation with the Soviet troops leaving the authority to Armenian Bolsheviks and left Artsakh with his military unit. 31
Keywords: Հայոց պատմություն